Characterization of livestock production units in Aldama, Tamaulipas, Mexico: producers, herd, and animal feed - Garay Martínez, Jonathan Raul; Godina Rodríguez, Juan Eduardo; Hernández Rodríguez, Blas; Maldonado-Torres , Aracely; López-Cantú, David Gilberto; Joaquín Cancino, Dr. Santiago (Ecosistemas y Recursos Agropecuarios, 2025)
Characterizing livestock production units (LPUs) allows us to suggest technologies that counteract problems and increase productivity. The objective of this study was to characterize the producers, herd and animal feed in LPUs in the municipality of Aldama, Tamaulipas, Mexico, where 49 producers who own LPUs of beef cattle participated. For the analysis of the information, descriptive statistics and Excel (Microsoft®) were used. The average age of the owners was 58 ± 14 years and 85% can read and write. The area dedicated to grazing is 119 ± 51 ha and livestock farming is mainly extensive (55%), where the pastures present are African star grass (Cynodon, 35%), Guinea grass (Megathyrsus, 25%) and hurricane grass (Bothriochloa, 24%). The 64% of the producers mentioned that drought is the main problem. The main bovine genotypes used are crosses of zebu cattle and specialized meat breeds (66%). The herd consists mainly of lactating (calving) and dry (pregnant) cows; 37%. Cattle graze all year round on the pastures, while supplementation and/or supplementation are used during the dry season (December-July). There are few innovations adopted with respect to technified grazing (6 %), forage conservation (5%), and pasture establishment (4%). The drought causes a decrease in the availability of fodder and producers, not having the training or resources to produce fodder, have to resort to the purchase of hay, silage, concentrates and grains, which increases production costs in the LPUs.